Cuffed endotracheal tubes in children: the effect of the size of the cuffed endotracheal tube on intracuff pressure. Issue 5 (15th February 2017) - Krishna, Senthil G.; Hakim, Mumin; Sebastian, Roby; Dellinger, Heather L.; Tumin, Dmitry; Tobias, Joseph D.
Summary: Background: In children, the size of the cuffed endotracheal tube is based on various age‐based formulas. However, such formulas may over or underestimate the size of the cuffed endotracheal tube. There are no data on the impact of different‐sized cuffed endotracheal tubes (ETT) on the intracuff pressure in children. Aim: The current study measures intracuff pressure with different‐sized cuffed ETT. Method: The study was conducted in an in vitro and in vivo phase. For the in vitro phase, 10 cuffed ETT of size 4.0, 4.5, and 5 mm internal diameter (ID) each were randomly placed inside a 1.0 cm ID plastic tube (mimicking the trachea), which was in turn connected to a 1 l test lung. After inflation of the cuff using the air leak test at a continuous positive airway pressure of 20 cmH2 O, the intracuff pressure was measured. The in vivo phase was conducted in 100 children (4–8 years) and were randomly divided into two groups to receive either a cuffed endotracheal tube based on the Khine formula (Group R) or a cuffed endotracheal tube that was a half‐size (0.5 mm ID) smaller (Group S). Following the inflation of the cuff to seal the trachea, the intracuff pressure was measured. Results: In the in vitro phase, the intracuff pressure was 45 ± 6, 23 ± 1, and 14 ± 6 cmH2 O with size 4.0, 4.5, and 5 mm ID cuffed ETT, respectively ( F ‐test P < 0.001 for difference among three groups). In the in vivo phase, the mean intracuff pressure in Group R was 25 ± 19 cmH2 O vs 37 ± 35 cmH2 O in Group S (95% CI of difference: 1, 23; P = 0.039). Conclusion: If the cuffed endotracheal tube is too small, the trachea can still be sealed by inflating the cuff with additional air. However, this transforms the cuff from the intended high‐volume, low‐pressure cuff to an undesirable high‐volume, high‐pressure cuff. Abstract :